KAJIAN BENTUK DAN MAKNA LAGU œGAMBIRI TOPI PASAR DI DESA SARIMATONDANG KECAMATAN SIDAMANIK KABUPATEN SIMALUNGUN - Purba, Chrismay Denny (Universitas Negeri Medan, 2018)
The purpose of this research is to know the origin of Gambiri Topi Pasar song, to know the formof Gambiri Topi pasar song, to know the meaning contained in Gambiri Topi Pasar song, toknow the character of Gambiri Topi Pasar song, to know how the response of Simalungunsociety in Sarimatondang Village Sidamanik District Simalungun Regency against Gambiri TopiPasar song.The theory used in this research is the theory of study that explains the definition of study that is ordescribes a detailed matter so that the review, music theory is music is a cultural activity that isvery familiar with human life, the form theory is the form is a scheme or a whole structure fromseveral phrases, the theory of meaning that uses the theory of semiotics and semantic theory, thetheory of Gambiri Topi Pasar song is a story that describes the relationship of romance betweenyoung people.The method in this research is descriptive qualitative method. Based on the results of researchconducted it can be seen that the origin of the song Gambiri Topi Pasar is an ethnic song inheritedfrom the ancestors of the community Simalungun to generation hereditary orally. His trademarkuses Inggou Simalungun. The Gambiri Topi Pasar form of the song consists of two forms: formA consists of phrases a and a'. form B consists of the phrases b and b'. The meaning of GambiriTopi Pasar song is an individual meaning that is now used as a death song.